Promotion of socio-emotional skills in peers of children with Cerebral Palsy: the perspective of educational agents (Revista Lusófona de Educação, 2025)
Including children with Cerebral Palsy in preschool can benefit all students, helping to foster important socio-emotional skills and preparing them for life in society. The perspective of educational agents on this subject is fundamental for this study. This project aims to i) contextualize and characterize the process of inclusion and participation of children with Cerebral Palsy in preschool; ii) explore the perception of educational agents about the socio-emotional skills of peers of children with Cerebral Palsy and iii) identify strategic barriers that favor the development of these social-emotional skills. The study involved ten Educational Agents: four Educational Action Helpers, four Childhood Educators, an Early Intervention technician, and a Special Education teacher. Data was collected from semi-structured interviews, and then imported into WebQDA for analysis and categorization after coding. The results identified barriers to promoting socio-emotional skills and activities relevant to developing these skills.Key barriers are few human resources and communication difficulties. The most developed skills considered are valuing diversity and managing relationships. In an inclusive environment, peers of children with CP learn to understand and respect differences, practice empathy and solidarity, collaborate, and resolve conflicts. Obstacles to developing these skills included insufficient human resources and some adult attitudes stemming from a lack of training.The study revealed that educational agents' perspectives align with current concepts of belonging and inclusion. It also emphasized the crucial role of educators in fostering inclusive environments. The findings indicate that children with cerebral palsy are sought out by their peers for help and play, suggesting a potentially inclusive and protective preschool environment. This study underscores the importance of promoting social-emotional competencies in preschool children.